OP0047 Osteoporotic hip fracture prevention: are we in a crisis?. (15th June 2017) - Sehgal, M; Mithal, A; Mithal, A; Singh, G
Abstract : Background: Osteoporotic hip fractures are a significant cause of morbidity and mortality in the elderly. With the aging of the US population, it was expected that there would be a nationwide "epidemic" of osteoporotic fractures; however, Medicare reimbursement for osteoporosis screening and the rapid uptake of bisphosphonate therapy in the late 1990s and early 2000s probably forestalled this epidemic. In fact, osteoporotic hip fractures numbers declined during this time, despite the dramatic growth of the elderly population (1). However, bisphosphonate prescriptions have dropped precipitously by over 50% from their peak in 2008 (2), likely because of concerns regarding their adverse events. In this era of "crisis" in osteoporosis prevention, has the pendulum swung back on hip fracture numbers? Objectives: To study the number and prevalence of osteoporotic hip fractures in patients 50 years and older over the last 22 years (1993–2014) in the US? Methods: The Nationwide Inpatient Sample (NIS) is a stratified random sample of all US community hospitals. It is the only US national hospital database with information on all patients, regardless of payer, including persons covered by Medicare, Medicaid, private insurance, and the uninsured. We examined all inpatient hospitalizations in NIS from 1993 to 2014 with a primary diagnosis of non-traumatic hip fractures, and calculated age-adjusted prevalence rates. We excluded patients with concomitant diagnosis of major trauma, primary or secondary tumors locally, osteopetrosis and procedures for revision surgery or surgery for complications. US population estimates and projections for the resident US population were obtained from the US Census Bureau. Results: There were 407 million all-cause hospitalizations in 1.88 billion person-years of observation among people 50 years of older from 1993 to 2014 (21, 626 hospitalizations per 100, 000 person-years). During this time-period, there were 6.15 million hospitalizations for osteoporotic hip fractures in this population (327 per 100, 000 person-years). After an initial increase in hip fractures from 1993 to 1996, there was a decline of 10.6% in total number of hip fractures from 300, 154 in 1996 to 268, 356 in 2010 even though population of 50 years and older increased from 69.9 million to 99.6 million in the same time. After bottoming out in 2010, the total number of hip fractures increased by 6.2% to 285, 050 in 2014 (Figure, blue broken line). However, the age-standardized prevalence rate of hip fractures declined steadily (from 414/100, 000 in 1996 to 269/100, 000 in 2014, p<0.0001, Figure solid red line), although the rate of decline has ameliorated somewhat from 2010 onwards (not statistically significant). Conclusions: The total number of osteoporotic hip fractures in 50 years and older declined since 1996, bottomed out in 2010 but has started increasing again. It is critical to evaluate risks and benefits of preventive treatments for optimal management of this potentially serious problem. References: Sehgal, A., et al., A victory in the war on osteoporosis? Declining prevalence of hospitalizations for non-traumatic hip fractures in the US. Ann Rheum Dis 2008;67(Suppl II):55. Wysowski, D.K. and P. Greene, Trends in osteoporosis treatment with oral and intravenous bisphosphonates in the United States, 2002–2012. Bone, 2013. 57(2): p. 423–8. Disclosure of Interest: None declared